2019
DOI: 10.26650/ekoist.2018.14.29.0013
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Connection amongst Renewable Energy, Economic Growth and Carbon Dioxide Emissions in Algeria

Abstract: In this paper, we shall study the relationship between renewable energy, economic growth (GDP), carbon dioxide emissions and with control variable that are estimated into realized volatility and to verify if the EKC hypothesis is accepted or not. This study is focussed on the Algerian situation during the periods of 1995-2016 and we employed the VECM procedure and Granger causality to estimate the short and long-run coefficients. We found with VECM that an increase in carbon dioxide emissions, fossil energy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 1 publication
1
18
0
Order By: Relevance
“…They established that the EKC hypothesis is not valid, because the expansion in production level will not stop the USA’s growth and will create a collapse in the environment. Sari-Hassoun et al ( 2019 ) investigated the link between fossil energy, renewable energy, carbon dioxide emissions, and economic growth in Algeria during the period of 1995–2016. To analyze the influence in the short and long term, they used Granger causality and the vector error correction model (VECM).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…They established that the EKC hypothesis is not valid, because the expansion in production level will not stop the USA’s growth and will create a collapse in the environment. Sari-Hassoun et al ( 2019 ) investigated the link between fossil energy, renewable energy, carbon dioxide emissions, and economic growth in Algeria during the period of 1995–2016. To analyze the influence in the short and long term, they used Granger causality and the vector error correction model (VECM).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Friedlingstein et al ( 2010 ), they noticed that before 2100, the quantity of carbon will increase by 9 times than now and it is going to reach an unbelievable quantity of carbon that the atmosphere would not be able to support. Therefore, such outcomes push policymakers to search for solutions to the coming environmental disaster (Ke et al 2022 ; Sari-Hassoun et al 2019 ). The depletion of natural resources and pollution has become a severe issue that necessitates a rethinking of current government policy (Sharif et al 2020b ; Jahanger et al 2022b ; Usman and Balsalobre-Lorente 2022 ; Sari-Hassoun and Ayad 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, Lacheheb et al (2015) found that the EKC does not exist for Algeria over the period 1971–2009. In the same vein, Sari Hassoun et al (2018) investigated the nexus amongst renewable energy, economic growth and CO 2 emissions in Algeria over the period 1995–2016 and found that an increase in GDP and energy consumption upsurge the level of carbon emissions. Amri (2017) identified the linkage between nonrenewable energy consumption, renewable energy consumption, economic growth and CO 2 emissions in Algeria during 1980–2011.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A number of investigations showed the importance to include the renewable energy into the energy system and its positive relationship with the economic growth (Inglesi-Lotz, 2016; Rafindadi and Ozturk, 2017; Armeanu et al, 2017;Koçak and Şarkgüneşi, 2017;Atems and Hotaling, 2018;Adams et al, 2018;Sari Hassoun and Mekidiche, 2019). These scholars employed different methodologies with several econometrics models, and they used many control variables such as the gross fixed capital formation (capital), the labour force, the non-renewable energy consumption and production, institution variables…etc.…”
Section: Literature Reviewmentioning
confidence: 99%